Pengaruh Penerapan Metode Outdoor Learning Dengan Memanfaatkan Barang Bekas Terhadap Hasil Belajar Siswa Pada Pembelajaran Tematik - Ady Darmansyah; Abdul Muktadir; Dwi Anggraini (Universitas Bengkulu, 2021)
The study aims to determine the effect of outdoor learning method by utilizing used goods on learning outcomes in Thematic learning in grade IV SD Group 11 Bengkulu City. This type of research is a quasi-experimental research with the design of the study of the matching only pretest-posttest control group design. The population in this study is all students of class IV SD group 11 consisting of 7 elementary schools. Based on the homogeneity test results, the sample in this study were the students of grade IV B SDN 44 as the experimental class and the students of class IV A SDN 55 as the control class. The research instrument used is; (1) a matter of objective test consisting of 30 items;(2) attitude observation sheet; and (3) skill observation sheet. Data analysis used is descriptive analysis, prerequisite test and inferential analysis that is t-test. Based on data analysis of research results, obtained the average value of posttest result of experimental class using outdoor learning method that is 72,00 and control class using conventional learning that is 67,50. T-test of both sample classes with significance level ? = 0.05, obtained count = 4,241 whereas ttable = 1,680, tcount > ttable so that H0 is rejected and Ha accepted. The increase of research result percentage in experiment class is higher than control class that is 75,31% in experimental class and control class 64,87%. Thus it can be concluded there is a significant effect of student learning outcomes that follow the learning using outdoor learning method.